Oxygenated monoterpenes-rich volatile oils as potential antifungal agents for dermatophytes. Issue 4 (16th February 2017) - Dias, N.; Dias, M.C.; Cavaleiro, C.; Sousa, M.C.; Lima, N.; Machado, M.
Abstract: Essential oils (EOs) extracted from Lavandula luisieri and Cymbopogon citratus were tested for their antifungal activity against ten clinical isolates of dermatophytes isolated from cases of tinea pedis. Inhibition of conidial germination and antifungal drug/EO combination assay were tested on two ATCC reference strains of Trichophyton rubrum and Trichophyton mentagrophytes . EOs were characterised by high amount of oxygenated monoterpenes in their composition. Strong antifungal activity was observed for the majority of clinical strains, and fungicidal activity was demonstrated. Positive interaction between L. luisieri EO combined with terbinafine was observed against terbinafine-resistant strain ( Tr ATCC MYA-4438). Significative reduction of the germination was observed above 100 μg mL −1 . Both oils were safe to macrophage mammalian cells at tested concentration. This study describes the antifungal activity of L. luisieri and C. citratus EOs against dermatophytes, which could be useful in designing new formulations for topical treatments. Abstract :